Psychogenic nonepileptic seizures treated as epileptic seizures in the emergency department. (15th August 2021) - Lehn, Alexander; Watson, Emily; Ryan, Elizabeth G.; Jones, Maryon; Cheah, Vince; Dionisio, Sasha
Abstract: Objectives: We aimed to estimate the rate of psychogenic nonepileptic seizures (PNES) among patients presenting to an emergency department with presumed seizures. We also wanted to identify factors that can assist health care professionals in determining whether these events are likely to be epileptic or nonepileptic. Methods: We performed two retrospective audits on patients who were treated for seizures in the department of emergency medicine at the Princess Alexandra Hospital, Brisbane, Australia. Exploratory analyses and logistic regressions were conducted to investigate the characteristics of the presentations and the relationships between our variables of interest. Results: In the group of all presentations with presumed seizures over a 3‐month period ( n = 157), a total of 151 presentations (96.2%) presentations were given a primary diagnosis of epileptic seizures. Of these 151 presentations, only 84 (55.6%) presented with epileptic seizures and 40 (26.5%) actually presented with PNES. In the group of patients who presented with prolonged and/or multiple events ( n = 213) over a 1‐year period, 196 (92.0%) were treated as epileptic seizures. Of these 196 presentations, only 85 (43.4%) presented with epileptic seizures and 97 (49.5%) actually presented with PNES. Several factors were identified to help risk stratify between epileptic seizures and PNES: Duration of events and of the postictal phase, number of events, presence of a structural brain pathology, mental health history, lactate levels and presence of tongue bite, incontinence, and/or vomiting. Significance: A large proportion of people who present to emergency departments with events resembling epileptic seizures actually have PNES rather than epilepsy—particularly those patients who present with prolonged and/or multiple events. The rate of misdiagnosis was high. Efforts need to be made to recognize patients with psychogenic nonepileptic seizures earlier and diagnose them correctly to avoid unnecessary iatrogenic harm and to provide adequate treatment.